Biochemical and Muscle Mechanical Postmarathon Changes in Hot and Humid Conditions. Issue 3 (March 2020) - Gutiérrez-Vargas, Randall; Martín-Rodríguez, Saúl; Sánchez-Ureña, Braulio; Rodríguez-Montero, Alejandro; Salas-Cabrera, Jorge; Gutiérrez-Vargas, Juan C.; Simunic, Bostjan; Rojas-Valverde, Daniel
Abstract : Abstract: Gutiérrez-Vargas, R, Martín-Rodríguez, S, Sánchez-Ureña, B, Rodríguez-Montero, A, Salas-Cabrera, J, Gutiérrez-Vargas, JC, Simunic, B, and Rojas-Valverde, D. Biochemical and muscle mechanical postmarathon changes in hot and humid conditions. J Strength Cond Res 34(3): 847–856, 2020—The aim of this study was to compare biochemical changes and mechanical changes in the lower-limb muscles before and after a marathon race in hot and humid conditions. Eighteen healthy runners participated in a marathon at between 28 and 34° C and 81% humidity in Costa Rica. Serum magnesium (Mg 2+ ), creatine phosphokinase (CPK), lactate dehydrogenase, and hematocrit (HCT) were measured before and after the marathon. Tensiomyography measurements from the rectus femoris (RF) and vastus medialis, muscle displacement (Dm), contraction time (Tc), and velocities of contraction to 10 and 90% of Dm (V10 and V90 ) were obtained before and after the marathon. Postrace measurements showed a 544% increase in CPK ( t (17): −6.925, p < 0.01), a 16% increase in HCT ( t (17): −7.466, p < 0.01), a 29% decrease in Mg 2+ ( t (17): 3.91, p = 0.001), a 2% decrease in body mass ( t (17): 4.162, p = 0.001), a 4% increase in Tc of the RF ( t (17): −2.588, p = 0.019), and a 12% increase in Dm of the RF ( t (17): −2.131, p < 0.048) compared with prerace measurements. No significant biochemical or mechanical differences were found between runners in terms of their finish times. These findings showed that completing a marathon in hot and humid conditions induced a significant reduction in lower-limb muscle stiffness, body mass, and Mg 2+, and increased neuromuscular fatigue, CPK, and HCT, because of muscle damage and dehydration. Knowledge of the effects of heat and humidity may be of value for coaches and sports medicine practitioners in developing effective hydration and recovery protocols for marathon runners in these special conditions.